Cinema and the Algerian War of Independence Culture, Politics, and Society - Baǧāwī, Aḥmad (Palgrave Studies in Arab Cinema, 2020)
Intro -- Foreword: Algerian War of Resistance, a War of Images -- Praise for Cinema and the Algerian War of Independence -- Contents -- Acronyms -- List of Figures -- 1 Introduction -- 2 Popular Resistance at the Origin of the National Movement -- Going Back in History -- Bouamama, El-Mokrani, and the Great Revolts -- The Fiction-Documentary and the "Outlaws" -- Lifting the Veil on the Colonial Night -- The Battle of Cannes … -- The Other May 8, 1945 -- Small Arrangements and Timid Recognition -- Prelude to the Unrest -- Awakening Memories -- 3 Freedom Filmmakers: Pioneers in the Information Battle -- From Guns to the Media -- The Battle of Communication -- Filmmaker-Pioneers -- Djamel Chanderli and the "Image and Sound" Service -- René Vautier -- Pierre Clément -- Yann Le Masson -- Cécile Decugis -- Stevan Labudovic, Zdravko Pecar, and Karl Gass -- Jacques Charby -- From the Image and Sound Cell to the Cinema Service -- The Camera and the Gun for Freedom -- 4 Dream and Hope in Images: Algeria, Mirror Image of Its Cinema -- Moussaoui and the Archives -- New Structures -- The Battle of Algiers -- Three War Film Classics -- Then Came Zinet … -- Another View of the War -- War Films or Films About the War? -- An Inexorable Decay -- Fresh Start -- What Happens Next? -- 5 October in Paris: Panijel Et Al. -- Case Study: Who Remembers Jacques Panijel? -- 6 War on Screens in France and Elsewhere: From Cautiousness to the Awakening of Memories -- War Censorship -- Lost Soldiers -- Courrière and the Rest -- Conscientious Objectors -- Suitcase Carriers and the FLN Support Networks -- The New Wave and the Algerian War -- Reintegration and The Dove's Lost Collar -- Comparative Viewpoints: The Improbable Equation -- Researching History and Archive Documentaries -- When Fiction Reveals Traumas -- Public, Censor, and Amnesia.